Photobiomodulation (PBM) irradiation enhances the therapeutic potential of hMSC spheroids for neural repair - Chang, So-Young; Hong, Namgue; Choi, Ji Eun; Ahn, Jin-Chul; Lee, Min Young (Frontiers in Cellular Neuroscience, 2026)
Neural regeneration remains a critical goal in regenerative medicine, especially for treating central nervous system injuries such as stroke, spinal cord injury, and neurodegenerative diseases. Mesenchymal stem cells (MSCs) have shown therapeutic potential through their capacity for differentiation and paracrine signaling; however, their clinical application is limited by low survival and engraftment rates. In this study, we investigated whether the therapeutic efficacy of human MSC (hMSC) spheroids could be enhanced through photobiomodulation (PBM). hMSCs were aggregated into three-dimensional spheroids and divided into four experimental groups: (1) untreated control spheroids, (2) spheroids treated with 660 nm PBM, (3) spheroids treated with 850 nm PBM, and (4) spheroids co-cultured with primary rat cortical neurons subjected to oxidative stress using hydrogen peroxide (H₂O₂). The PBM groups were exposed to red (660 nm) or near-infrared (NIR; 850 nm) light for 10 min. Neuronal viability and axonal regeneration were assessed. Our results demonstrated that PBM-treated hMSC spheroids significantly increased neuronal survival and axonal outgrowth compared to H₂O₂-only controls, particularly under high oxidative stress conditions. Notably, spheroids treated with 850 nm PBM exhibited the most robust neuroprotective effects. These findings suggest that PBM enhances mitochondrial activity and the secretion of neurotrophic factors by hMSC spheroids, thereby promoting neuroregeneration. This combinatorial strategy integrating PBM with 3D stem cell spheroid culture offers a promising avenue for developing advanced stem cell therapies for neurological disorders.